Creatine does not promote hypertrophy in skeletal muscle in supplemented compared with nonsupplemented rats subjected to a similar workload - Aguiar, Andreo Fernando [UNESP]; Alves de Souza, Rodrigo Wagner [UNESP]; Aguiar, Danilo Henrique; Milanezi Aguiar, Rachel Colauto [UNESP]; Vechetti, Ivan Jose [UNESP]; Dal-Pai-Silva, Maeli [UNESP] (Pergamon-Elsevier B.V. Ltd, 2011)
The purpose of this study was to test the hypothesis that creatine (Cr) supplementation may promote an additional hypertrophic effect on skeletal muscle independent of a higher workload on Cr-supplemented trained muscle compared with Cr-nonsupplemented trained muscle. Male Wistar rats (2-3 months old, 250-300 g) were divided randomly into 4 groups (n = 8 per group): nontrained without Cr supplementation (CO), nontrained with Cr supplementation (CR), trained without Cr supplementation (TR), and trained with Cr supplementation (TRCR). Creatine supplementation was given at 0.5 g/kg per day. Trained groups were submitted to a 5-week resistance training program (5 d/wk). The progressive workloads were similar between the Cr-supplemented (TRCR) and Cr-nonsupplemented (TR) trained groups; the only difference between groups was the Cr treatment. After the 5-week experiment, the soleus muscle was dissected to analyze the cross-sectional area (CSA) of the muscle fibers. Resistance training promoted a significant (P < .05) increase in the muscle fibers CSA in the TR group compared with the CO group. However, no additional hypertrophic effect was found when Cr supplementation was added to training (TRCR vs TR comparison, P > .05). In addition, Cr supplementation alone did not promote significant alterations in muscle fiber CSA (CR vs CO comparison, P > .05). We conclude that Cr supplementation does not promote any additional hypertrophic effect on skeletal muscle area when Cr-supplemented trained muscles are submitted to same training regimen than Cr-nonsupplemented trained muscles. Specifically, any benefits of Cr supplementation on hypertrophy gains during resistance training may not be attributed to a direct anabolic effect on the skeletal muscle. (C) 2011 Elsevier B.V. All rights reserved.
Keywords: Soleus muscle; Weight training; Cross-sectional area; Nutritional intervention; Rodent